2017
DOI: 10.1111/pace.13112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment crossovers on clinical outcomes in the rate and rhythm control strategies for atrial fibrillation: Insights from the AFFIRM (Atrial Fibrillation Follow‐up Investigation of Rhythm Management) trial

Abstract: We investigated the rates and reasons for crossover to alternative treatment strategies and its impact on mortality in patients who were enrolled in the Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial. Over a mean follow-up period of 3.5 years, 842 patients underwent crossover to the alternative treatment arms in AFFIRM. The rate of crossover from rhythm to rate control (594/2,033, 29.2%) was more frequent than the rate of crossover from rate to rhythm control (248/2,027, 12.2%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The landmark Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial, comparing these 2 strategies, failed to show a significant benefit for the rhythm control strategy over rate control. 8 However, subsequent subanalyses have suggested that although sinus rhythm is beneficial, this is offset both by adverse effects associated with antiarrhythmic drugs (AADs) used for the purpose as well as by the relatively poor efficacy of drugs in maintaining sinus rhythm in a good proportion of patients, 9, 10 In discussing the need for, as well as strategies for rhythm control in AF, it is useful to separately consider acute and chronic rhythm control.…”
Section: Rate Control Versus Rhythm Control In Afmentioning
confidence: 99%
“…The landmark Atrial Fibrillation Follow-up Investigation of Rhythm Management (AFFIRM) trial, comparing these 2 strategies, failed to show a significant benefit for the rhythm control strategy over rate control. 8 However, subsequent subanalyses have suggested that although sinus rhythm is beneficial, this is offset both by adverse effects associated with antiarrhythmic drugs (AADs) used for the purpose as well as by the relatively poor efficacy of drugs in maintaining sinus rhythm in a good proportion of patients, 9, 10 In discussing the need for, as well as strategies for rhythm control in AF, it is useful to separately consider acute and chronic rhythm control.…”
Section: Rate Control Versus Rhythm Control In Afmentioning
confidence: 99%
“…Indeed, in both the A Comparison of Rate Control and Rhythm Control in Patients with Atrial Fibrillation (AFFIRM) and Rhythm Control versus Rate Control for Atrial Fibrillation and Heart Failure (AF-CHF) trials-the 2 landmark studies which investigated medical rate control versus medical rhythm control for the treatment of AF in the general population and in the HF population, respectively-worsening HF symptoms were the most common reasons to abandon a rate control strategy in favor of a rhythm control strategy. [10][11][12] Just as reversion to sinus rhythm may benefit patients with AF and HF, the development and persistence of AF may cause substantial harm. This is especially true for patients with HF with reduced ejection fraction (HFrEF) and AF.…”
Section: Mechanistic Links Between Af and Hfmentioning
confidence: 99%
“…Furthermore, we hypothesize that, because of the potential adverse drug effects (including lethal side effects) of antiarrhythmic drugs (AAD), older patients and those with more comorbidities are more likely to be prescribed a rate control strategy. 19,20…”
Section: Introductionmentioning
confidence: 99%